A Concise Introduction to Mechanics of Rigid Bodies Multidisciplinary Engineering - Huang, L. (Springer International Publishing : Imprint: Springer, 2017)
This updated second edition broadens the explanation of rotational kinematics and dynamics - the most important aspect of rigid body motion in three-dimensional space and a topic of much greater complexity than linear motion. It expands treatment of vector and matrix, and includes quaternion operations to describe and analyze rigid body motion which are found in robot control, trajectory planning, 3D vision system calibration, and hand-eye coordination of robots in assembly work, etc. It features updated treatments of concepts in all chapters and case studies. The textbook retains its comprehensiveness in coverage and compactness in size, which make it easily accessible to the readers from multidisciplinary areas who want to grasp the key concepts of rigid body mechanics which are usually scattered in multiple volumes of traditional textbooks. Theoretical concepts are explained through examples taken from across engineering disciplines and links to applications and more advanced courses (e.g. industrial robotics) are provided. Ideal for students and practitioners, this book provides readers with a clear path to understanding rigid body mechanics and its significance in numerous sub-fields of mechanical engineering and related areas. Streamlines the treatment of rigid body motions in; one-, two, or three-dimensional spaces within an unified mathematical framework supported with vector, matrix, and quaternion operations; Maximizes reader understanding of analysis of rotational kinematics and dynamics; Explains theoretical concepts through examples taken from across engineering disciplines and provides linkages to applications and more advanced courses (e.g. industrial robotics); Features updated treatments of concepts in all chapters and case studies.